Beyond growth rate 0.6: Corynebacterium glutamicum cultivated in highly diluted environments. Issue 1 (13th August 2012) - Grünberger, Alexander; van Ooyen, Jan; Paczia, Nicole; Rohe, Peter; Schiendzielorz, Georg; Eggeling, Lothar; Wiechert, Wolfgang; Kohlheyer, Dietrich; Noack, Stephan
Abstract Fast growth of industrial microorganisms, such as Corynebacterium glutamicum, is a direct amplifier for the productivity of any growth coupled or decoupled production process. Recently, it has been shown that C. glutamicum when grown in a novel picoliter bioreactor (PLBR) exhibits a 50% higher growth rate compared to a 1 L batch cultivation [Grünberger et al. (2012) Lab Chip]. We here compare growth of C. glutamicum with glucose as substrate at different scales covering batch cultivations in the liter range down to single cell cultivations in the picoliter range. The maximum growth rate of standard batch cultures as estimated from different biomass quantification methods is <![CDATA[${\hat {\mu }} = 0.42\pm 0.03\, {\rm h}^{- 1} $]]> <inline-graphic xlink:href="ark:/27927/pgg1dwr0jxp" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> even for microtiter scale cultivations. In contrast, growth in a microfluidic perfusion system enabling analysis of single cells reproducibly reveals a higher growth rate of <![CDATA[${\hat {\mu }} = 0.62\pm 0.02\, {\rm h}^{- 1} $]]> <inline-graphic xlink:href="ark:/27927/pgg1dwr0jz7" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />. When in the same perfusion system cell‐free supernatant from exponentially grown shake flask cultures is used the growth rate of single cells is reduced to <![CDATA[${\hat {\mu }} = 0.47\pm 0.02\, {\rm h}^{- 1} $]]> <inline-graphic xlink:href="ark:/27927/pgg1dwr0k09" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />. Likewise, when fresh medium is additionally supplied with 5 mM acetate, a growth rate of <![CDATA[${\hat {\mu }} = 0.51\pm 0.01\, {\rm h}^{- 1} $]]> <inline-graphic xlink:href="ark:/27927/pgg1dwr0jfz" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> is determined. These results prove that higher growth rates of C. glutamicum than known from typical batch cultivations are possible, and that growth is definitely impaired by very low concentrations of byproducts such as acetate. Biotechnol. Bioeng. 2013; 110: 220–228. © 2012 Wiley Periodicals, Inc.